The Effect of Income on Job Satisfaction and Residential Satisfaction: A Literature Review - Bahare Fallahi, Aida Mehrad (Journal of Educational, Health and Community Psychology, 2015)
AbstractThe aim of present literature review paper is to identify vital role of income on the amount of job satisfaction and residential satisfaction. The findings of this study express that these two inner feeling factors have fundamental role on individualâs life. In addition, this study focused on value of income and its effect on job satisfaction and residential satisfaction. Moreover, low levels of income leads to various difficulties such as low level of job satisfaction and decrease of residential satisfaction among individuals and threaten their behaviors and reactions at work. Likewise, this issue provides insufficient situation in private life and decrease the quality of life.Key words: Job Satisfaction, Residential Satisfaction, Income, Quality of LifeÂ